What is chronic cough in children? - Ioan, Iulia; Poussel, Mathias; Coutier, Laurianne; Plevkova, Jana; Poliacek, Ivan; Bolser, Donald C.; Davenport, Paul W.; Derelle, Jocelyne; Hanacek, Jan; Tatar, Milos; Marchal, François; Schweitzer, Cyril; et al. (Frontiers in Physiology, 2014)
The cough reflex is modulated throughout growth and development. Cough – but not expiration reflex – appears to be absent at birth, but increases with maturation. Thus, acute cough is the most frequent respiratory symptom during the first few years of life. Later on, the pubertal development seems to play a significant role in changing of the cough threshold during childhood and adolescence resulting in sex-related differences in cough reflex sensitivity in adulthood. Asthma is the major cause of chronic cough in children. Prolonged acute cough is usually related to the long-lasting effects of a previous viral airway infection or to the particular entity called protracted bacterial bronchitis. Cough pointers and type may orient towards specific aetiologies, such as barking cough in croup or tracheomalacia, paroxystic whooping cough in Pertussis. Cough is productive in protracted bacterial bronchitis, sinusitis or bronchiectasis. Cough is usually associated with wheeze or dyspnea on exertion in asthma; however, it may be the sole symptom in cough variant asthma. Thus, paediatric cough has particularities differentiating it from adult cough, so the approach and management should be developmentally specific.